IMPLEMENTASI TEORI BELAJAR HUMANISTIK CARL R. ROGERS PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Muchamad Chairul Umam (Tadrib: Jurnal Pendidikan Agama Islam, 2019)
Education so far has not yet applied Humanistic learning which is actually very important because it has a goal that can shape students to be human so the researchers chose the topic of Humanistic learning so that education in schools can understand the potential possessed by students not only nature only positive fields. Humanistic learning initiated by Carl R. Rogers aims to shape learners' personalities not only in the cognitive aspect but more emphasized in the attitudes and social aspects, he also advocates an educational approach should try to make learning and teaching more human, more personal, and meaningful. Humanistic theory is a learning theory that tends towards philosophy, so that its implementation in learning PAI is still difficult to do in practical and operational learning steps, but the contribution is so large. The concepts, ideas, taxonomies of objectives that have been formulated can help educators and teachers in understanding human nature. This will be able to assist them in determining learning components such as goal formulation, material determination, selection of learning strategies, and development of evaluation tools, towards the formation of the aspired human. The research method used by researchers is qualitative by looking at social phenomena and understanding the meaning of human behavior. This research is descriptive in this study trying to explain or illustrate the implementation of Carl R Rogers' humanistic learning theory on Islamic religious learning.